Effects of bFGF on the Modulation of Apoptosis in Gingival Fibroblasts with Different Host Ages - Kotaro Tanimoto; Satoru Ohkuma; Yuki Tanne; Ryo Kunimatsu; Naoto Hirose; Tomomi Mitsuyoshi; Yuki Yoshimi; Shaoching Su; Kazuo Tanne (Hindawi Limited, 2013)
The purpose of this study was to investigate the effects of basic fibroblast growth factor (bFGF) treatment on the proliferation and apoptosis of cultured gingival fibroblasts (GFs). Human GFs were isolated from the palatal gingival tissues of 16 healthy volunteers ranging in the age from 9 to 35 years old. Cultured GFs were subjected to the analyses for cell proliferation by ELISA assay, gene expression by RT-PCR analysis, and apoptosis potency by caspase-3 assay. The cell proliferation activity and gene expression of type-I collagen and caspase-3 activity were enhanced significantly by the treatment with bFGF in cultured GFs. Furthermore, the activity of caspase-3 in cultured GFs from young subjects was significantly higher than that in GFs from adults. It is shown that bFGF significantly enhances the gene expression of type-I collagen in cultured fibroblasts from human gingival tissues. It also demonstrated that bFGF modulates the apoptosis of periodontal fibroblasts, and the effect is higher in young subjects, indicating a significant role of bFGF in the prevention of scar formation during wound healing.